STRATEGI PENGEMBANGAN SUBSEKTOR PERIKANAN DI KABUPATEN MALUKU TENGGARA BARAT, PROPINSI MALUKU - Yoseph ., Reressy; Leonardus R. Rengkung; Theodora M. Katiandagho (Sam Ratulangi University, 2016)
The objective of the study is: Analyzing a good strategy in the development of the Fisheries Resources in West Southeast Maluku District, so as to provide a decent income for communities and regions. This research is done by using the method of SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats) by looking at internal and external factors that exist. The research results indicate that internal factors, which become the strengths in the management of the fishery sector are the potential of Natural Resources, the availability of a reliable workforce, the potential of the sea in West Southeast Maluku District, improving the management of natural resources in the field of fisheries, and policies of the Government of the district in managing fishery sector. While the weakness of the internal factors are quality of human resources that are still relatively low, lack of education for the workers, the availability of infrastructure, lack of good understanding in technology, and lack of support from formal and informal institutions. External factors which become opportunity are regional autonomy, national policy for marine, support from the central government, and market potential. While the threats of external factors are the condition of the natural, social and cultural, illegal fishing, the limited supply of energy, and the price of the product which is not stable. In short, to improve the good management of the fishery sector in West Southeast Maluku District, then through a SWOT analysis, all elements of society in the district, especially the local government should optimize its strengths and opportunities that exist, as well as seeking alternative policies to reduce its weaknesses and threats which exist.